Mandibular condyle fractures and treatment methods - Ertunc Dayi; Ferhat Ayranci; Göksel Simsek Kaya; Mehmet Omezli (Cumhuriyet University, 2012)
Large majority of all mandibular fractures are localized on the condyle. Proper treatment of these fractures is important for preventing the functional and anatomic disorders that may occur subsequently.  However, the diagnosis and proper management of the fractured mandibular condyle is one of the controversial topics in maxillofacial trauma. In this paper, diagnosis and current treatment modalities of mandibular condyle fractures are reviewed. ÖZET Mandibula kırıklarının büyük bir kısmı kondiler sahada lokalizedir. Bu tip kırıkların uygun şekilde tedavisi bu bölgede daha sonradan oluşabilecek fonksiyonel ve anatomik bozuklukların gelişimini engellemek açısından büyük önem taşımaktadır. Bununla birlikte, kondil kırıklarının teşhis ve uygun tedavisi maksillofasiyal alanda tartışılan konulardan birisi olmuştur. Bu makalede, mandibular kondil kırıklarının teşhisi ve uygulanan tedavi yöntemleri gözden geçirilmiştir.Anahtar kelimeler: Kondil, açık redüksiyon, mandibula.